2009
DOI: 10.1029/2008jb005812
|View full text |Cite
|
Sign up to set email alerts
|

Heat source for an amagmatic hydrothermal system, Noto Peninsula, Central Japan

Abstract: Although there is no evidence of volcanism in the Noto Peninsula since the late Miocene, the peninsula has long been known to be unusual and atypical of non‐volcanic regions, as indicated by high‐temperature hot springs and a geothermal gradient greater than 50 K/km. In order to provide geochemical constraints on the heat source for amagmatic hydrothermal activity, the chemical and isotopic compositions of 14 gas and water samples from hot springs were measured. The observed 3He/4He ratios of most hot spring g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Previously published helium isotope data used in this study are from Craig et al [1978], Doğan et al [2006], Kita et al [1993], Kusakabe et al [2003], Marty et al [1989], Matsumoto et al [2003], Morikawa et al [2005], Murakami [2010], Nagao [2004], Nagao et al [1981], New Energy and Industrial Technology Development Organization [1988, 1990], Notsu et al [2001], Ohno et al [2011], Ohwada et al [2007], Okada et al [1994], Ono et al [1993], Sakamoto et al [1992], Sakata et al [1987], Sano and Wakita [1985], Sano and Marty [1995], Sano et al [1982, 1984, 1986, 1998a, 1998b, 2006, 2009], Sato et al [2002], Sturchio et al [1996], Takahata et al [2003], Umeda and Ninomiya [2009], Umeda et al [2006a, 2006b, 2007a, 2007b, 2009a, 2009b, 2011a, 2011b, 2012], Wakita et al [1987], and K. Asamori et al (unpublished data, 2012). The majority of samples measured in the previous studies were collected from wells and bubbling natural springs, the remainder are from volcanic gases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published helium isotope data used in this study are from Craig et al [1978], Doğan et al [2006], Kita et al [1993], Kusakabe et al [2003], Marty et al [1989], Matsumoto et al [2003], Morikawa et al [2005], Murakami [2010], Nagao [2004], Nagao et al [1981], New Energy and Industrial Technology Development Organization [1988, 1990], Notsu et al [2001], Ohno et al [2011], Ohwada et al [2007], Okada et al [1994], Ono et al [1993], Sakamoto et al [1992], Sakata et al [1987], Sano and Wakita [1985], Sano and Marty [1995], Sano et al [1982, 1984, 1986, 1998a, 1998b, 2006, 2009], Sato et al [2002], Sturchio et al [1996], Takahata et al [2003], Umeda and Ninomiya [2009], Umeda et al [2006a, 2006b, 2007a, 2007b, 2009a, 2009b, 2011a, 2011b, 2012], Wakita et al [1987], and K. Asamori et al (unpublished data, 2012). The majority of samples measured in the previous studies were collected from wells and bubbling natural springs, the remainder are from volcanic gases.…”
Section: Discussionmentioning
confidence: 99%
“…The mantle helium components of samples collected from the northern Chugoku region are relatively higher than those from northern Kyushu Island (Figure 3). [2007], Okada et al [1994], Ono et al [1993], Sakamoto et al [1992], Sakata et al [1987], Sano and Wakita [1985], Sano and Marty [1995], Sano et al [1982Sano et al [ , 1984Sano et al [ , 1986Sano et al [ , 1998aSano et al [ , 1998bSano et al [ , 2006Sano et al [ , 2009, Sato et al [2002], Sturchio et al [1996], Takahata et al [2003], Umeda and Ninomiya [2009], Umeda et al [2006aUmeda et al [ , 2006bUmeda et al [ , 2007aUmeda et al [ , 2007bUmeda et al [ , 2009aUmeda et al [ , 2009bUmeda et al [ , 2011aUmeda et al [ , 2011bUmeda et al [ , 2012, Wakita et al [1987], and K. Asamori et al (unpublished data, 2012). The majority of samples measured in the previous studies were collected from wells and bubbling natural springs, the remainder are from volcanic gases.…”
Section: Hydrogen Oxygen and Helium Isotopesmentioning
confidence: 99%
“…Although we have no conclusive argument for the origin of the low-velocity anomaly in the uppermost mantle beneath the Noto peninsula, we interpret that the low-velocity anomaly corresponds to a local uid-rich area in the uppermost mantle, from which uids have been supplied to the lower crust beneath the Noto peninsula over a geosocial time scale. Umeda et al (2009) showed that most hot springs in the Noto peninsula exhibit low 3 He/ 4 He ratios ranging from 0.03 to 1.2 Ra (Ra, the atmospheric 3 He/ 4 He ratio). However, 3 He/ 4 He ratios of two gas samples exceed 2.0 Ra (orange circles in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1a), and the two anomalous areas are located near the epicenters of the 1993 M6.6 Noto-Hanto-oki and 2007 Noto-Hanto earthquakes and the Noto earthquake swarm. Umeda et al (2009) interpreted that the two areas with high 3 He/ 4 He ratios are probably attributable to the local upward migration of uids with the mantle-derive helium and such uids may have triggered the 1993 and 2007 earthquakes. These observations support our hypothesis that the Noto earthquake swarm is caused by uids supplied from the uppermost mantle.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the spatial distribution of the air‐corrected 3 He/ 4 He ratios of gases from water samples around the source region of the 2000 western Tottori earthquake. Generally, the crustal helium component is expected to be dominant in water samples from wells in regions away from active volcanoes [e.g., Sano and Wakita , 1985; Umeda et al , 2009]. That is, the 3 He/ 4 He ratios would be lower than the atmospheric value owing to the addition to groundwater of radiogenic helium derived from decay of U and Th in crustal rocks during geologic time.…”
Section: Discussionmentioning
confidence: 99%